Postural Synergies and Their Development - Mark L. Latash; Vijaya Krishnamoorthy; John P. Scholz; Vladimir M. Zatsiorsky (Neural Plasticity)
The recent developments of a particular approach to analyzing motor synergies based on the principle of motor abundance has allowed a quantitative assessment of multieffector coordination in motor tasks involving anticipatory adjustments to self-triggered postural perturbations and in voluntary posturalsway. This approach, the uncontrolled manifold (UCM) hypothesis, is based on an assumption that the central nervous system organizes covariation of elemental variables to stabilize important performance variables in a task-specific manner. In particular, this approach has been used to demonstrate and to assess the emergence of synergies and their modification with motor practice in typical persons and persons with Down syndrome. The framework of the UCM hypothesis allows the formulation of testable hypotheses with respect to developing postural synergies in typically and atypically developing persons.